PRECISION VILLAGE DATA METHODOLOGY: A TRANSFORMATIVE APPROACH FOR SUSTAINABLE RURAL DEVELOPMENT IN INDONESIA - Ritha F Dalimunthe; Sri Fajar Ayu; Novita Anggraini; Arif Qaedi Hutagalung; Meutia Nauly; Ramadani Ramadani; Supriadi Supriadi; Muhammad Bangun Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The Precision Village Data (PVD) methodology has emerged as an innovative approach to addressing challenges in rural development by integrating census-based, spatial, and participatory data collection techniques. This study investigates the implementation of the PVD methodology in Denai Sarang Burung Village, Indonesia, to assess its effectiveness in improving governance, community welfare, and sustainable development planning. A mixed-methods approach combined quantitative data collection through surveys and Geographic Information Systems (GIS) mapping with qualitative insights from focus group discussions and key informant interviews. The findings reveal that the PVD methodology significantly enhanced data accuracy facilitated evidence-based decision-making, and promoted transparency in resource allocation. Community participation was a critical success factor, fostering trust and ownership among stakeholders. However, challenges such as limited digital infrastructure and capacity gaps among enumerators highlighted the need for further investments and training. The study concludes that the PVD methodology offers a robust framework for sustainable rural development and a scalable model for similar contexts globally. Future research should explore its application in diverse settings to evaluate long-term impacts and adaptability